The role of physiotherapy in prophylaxis and treatment of diabetic foot - Grigorief, Magdalena; Staniewska, Agata; Mysiak, Natalia; Frąckowska, Daria; Budzyński, Jacek (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2026)
Diabetes mellitus (DM) and its complications are a growing problem in contemporary healthcare. One of the most significant complications of DM is diabetic foot (DF). The aim of this paper is to present the current data concerning the role of the physiotherapist as an independent medical professional in primary and secondary DF prevention and in the care of patients with DF in order to reduce all-cause and cardiovascular mortality and the occurrence of major adverse cardiovascular events. As a member of a multidisciplinary team, the physiotherapist can: • diagnose the type and severity of functional status impairment, • recommend physiotherapeutic interventions for primary and secondary DF prevention, propose DF treatment and educate patients in self-management and the use of movement aids and limb prosthesis, • monitor the patient’s adherence to and the outcome of interventions.